PROMOTION IMPLEMENTATION THROUGH INSTAGRAM SOCIAL MEDIA AT GRAND JATRA HOTEL IN PEKANBARU - Andrian Hermawan; Teguh Widodo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The development of the hospitality bussiness causing increasingly fierce competition especially in markering side. Sales and Marketing Department is very influential on room sales and the promotion carried out by Grand Jatra Hotel in Pekanbaru. The implementation of promotion by making the hotel product more attractive and also known by the prospective consumer, so that they are more insterested in stay or buy other products. Therefore this research in purpose for knowing the promotion implementation and how respondents responds about promotion implementation through instagram social media at Grand Jatra Hotel in Pekanbaru. This research uses decriptive quantitative to analyze the problems based on data collections techniques in the forms of quistionnaires, observations and documentations. The promotion implementation through instagram social media includes advertisement text, pictures, audios, and videos. Based on the results of research that has been done, can be concluded that the promotion implementation through instagram social media has been done very well. But, in element of audio and video are not fully going well. Keywords : Social Media, Promotion, Hotel